2011
DOI: 10.1149/1.3597640
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Treatment Effects on Manganese Dioxide Structure, Morphology and Electrochemical Performance

Abstract: Kinetic analysis is used to determine the required isothermal heating time at various temperatures to theoretically completely remove water from an electrolytic manganese dioxide (EMD) sample. The effect of the heat treatment regime on material structure, morphology and composition is investigated using various physical techniques, including X-ray diffraction and gas adsorption. Further, the electrochemical performance of heat treated• EMD (HEMD) samples at a range of discharge rates finds that material proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…The investigation lead to a better understanding in this crucial area of battery material preparation and will aid in optimising the heat treatment processes that in turn can improve the overall performance of manganese dioxide as a cathode material in Li/MnO 2 primary cells. 158 Dose et al 48 discussed the post effect of heat treated manganese dioxide when it undergoes reduction in nonaqueous media. 156 and 157) showed that synthetic g-MnO 2 /EMD includes structural domains of ramsdellite and pyrolusite varieties, and that heat-treatment up to 400 C or elevated temperature lead to the progressive transformation of ramsdellite domains into pyrolusite domain, or with g-MnO 2 (orthorhombic unit cell) to b-MnO 2 (tetragonal unit cell).…”
Section: Treated Emdmentioning
confidence: 99%
“…The investigation lead to a better understanding in this crucial area of battery material preparation and will aid in optimising the heat treatment processes that in turn can improve the overall performance of manganese dioxide as a cathode material in Li/MnO 2 primary cells. 158 Dose et al 48 discussed the post effect of heat treated manganese dioxide when it undergoes reduction in nonaqueous media. 156 and 157) showed that synthetic g-MnO 2 /EMD includes structural domains of ramsdellite and pyrolusite varieties, and that heat-treatment up to 400 C or elevated temperature lead to the progressive transformation of ramsdellite domains into pyrolusite domain, or with g-MnO 2 (orthorhombic unit cell) to b-MnO 2 (tetragonal unit cell).…”
Section: Treated Emdmentioning
confidence: 99%
“…34,35 Current reports have suggested that EMD essentially consisted of epsilon-manganese dioxide (ε-MnO 2 ) or a mixture of γ-MnO 2 and ε-MnO 2 . [36][37][38] Mn 2+ + 2H 2 O → 2e − + 4H + + MnO 2 (Anode) [10] 2H + + 2e − → H 2 (Cathode) [11] …”
Section: Resultsmentioning
confidence: 99%
“…γ-MnO 2 is described as an intergrowth between Pyrolusite and ramsdellite-forms of MnO 2 [ 27 ]. The as-prepared EMD contains water in its film structure [ 48 ]. In order to enable reversibility and avoid lithium hydroxide formation upon Li-ion intercalation tests, removal of water from EMD thin films is necessary.…”
Section: Introductionmentioning
confidence: 99%